(untitled) (Journal of Science and Technology Research, 2024)
The purpose of this study is to look at the seminal characteristics of short-term stored spermatozoa (at 4°C) from indigenous Aseel chickens in Bangladesh. The abdominal massage technique was utilized to collect semen from adult Aseel chickens at 3-day intervals and microscopically analyze the semen quality. The semen was then diluted with egg yolk-citrate (EYC) extender and stored at 4°C. They were then evaluated at various storage times, including Day 0 (0 hours), Day 1 (24 hours), Day 2 (48 hours), Day 3 (72 hours), Day 4 (96 hours), and Day 5 (120 hours). The findings of the study revealed that as storage time progressed, sperm motility, live spermatozoa, and the percentage of normal spermatozoa decreased. Total motility percentage significantly (P<0.05) decreased with the extended storage time in case of all individual cock. Progressive motility percentage was significantly (P<0.05) decreased from Day 0 (57.4±3.21) to Day 5 (0.11±3.21). On the contrary, non-motile sperm percentage significantly increased in Day 5 (99.3±4.85) compared to Day 1 (21.9±4.85). On the other hand, live spermatozoa were significantly (P<0.05) higher (76.68±5.06%) on Day 0 (0 h) and gradually declined day after day and finally it was 0% on day 5 (120 h). Similarly, spermatozoa abnormalities were highest at Day 5 (11.29±1.69% head, 3.33±1.42% mid-piece and 7.26±1.66% tail) and head abnormalities were significantly (P<0.05) affected by the storage time. Therefore, this study concluded that the storage duration had a substantial impact on the quality of Aseel chicken sperm, which may be used for artificial insemination (AI). The outcomes of this study may be valuable for the conservation and enhancement of the indigenous Aseel chicken breed in Bangladesh through the use of AI. J. of Sci. and Tech. Res. 6(1): 65-72, 2024